How gacha gaming and life quality shape problem gambling risk: insights from a cross-sectional study using Hong Kong-based online survey of young adults - Tang, Anson Chui Yan; Kwan, Rick Yiu Cho; Wong, Eliza Mi Ling; Cheng, Winnie Lai Sheung (Frontiers in Psychiatry, 2025)
BackgroundResearch related to the effects of gacha gaming on problem gambling among Chinese young adults in Hong Kong is limited the impact of quality of life (QoL) domains on gacha-related gambling behaviors remains largely unexplored. This study explored associations between gacha gaming behaviors QoL problem gambling risk in this population.MethodsA cross-sectional study used an online survey to collect data from 281 young adults (aged 18–25) with experience in freemium gaming. Participants completed questionnaires on socio-demographics, problem gambling risk (PGSI-C), QoL (WHOQOL-BREF, Hong Kong version), and gacha gaming behaviors (e.g., daily gaming time, monthly expenses). Stepwise regression analyzed associations between PGSI scores, QoL domains, and gaming behaviors, with p<0.05 indicating significance.ResultsOf 281 respondents, 63.3% belonged to the low-risk problem gambling group, and 11% belonged to the high-risk group. High-risk gamers had significantly higher monthly gacha expenses (p=0.021). Regression analysis revealed a significant association between PGSI scores, daily gaming time, QoL variables, and education level(Adjusted R²=0.113, p=0.001). Physical and overall QoL were negatively associated with problem gambling risk(p<0.01), while daily gaming time and social QoL were positively associated with problem gambling risk(p<0.05,p<0.01). Effect sizes of all significant variables were small (f²=0.014–0.04).ConclusionsThe positive association between social QoL and problem gambling risk suggests that a gamer’s social circle significantly influences gambling behavior. These findings provide direction for future studies on the contributing roles of different QoL domains in gacha-related gambling among Chinese young adults in Hong Kong. Future studies shall adopt a probability sampling approach and/or a wider sampling pool to increase the generalizability of the findings.